2018
DOI: 10.1080/23766808.2018.1467173
|View full text |Cite
|
Sign up to set email alerts
|

Diet and first report of batracophagy inLeptodactylus podicipinus(Anura: Leptodactylidae)

Abstract: In this study, we describe the diet of Leptodactylus podicipinus in South Pantanal. We analysed the stomach content of 30 individuals collected in September 2017 in the Miranda sub-region, Mato Grosso do Sul. We identified 19 prey categories to Order level, out of which Coleoptera was the most representative group and the most important prey category, followed by Orthoptera and Hemiptera. We recorded a post-metamorphic individual of Rhinella schneideri in the diet of L. podicipinus, the first record of batraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(26 reference statements)
0
3
2
Order By: Relevance
“…In this study, we observed differences in relation to previous studies, for instance, the one by Ceron et al ., (2018) , which also analyzed the diet of Leptodactylus podicipinus , belonging to the same Leptodactylus melanonotus species group, where the prey category with the highest IVI was Coleoptera; however, the L. petersii individuals analyzed in this study had Hymenoptera (Formicidae) as the most representative item.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In this study, we observed differences in relation to previous studies, for instance, the one by Ceron et al ., (2018) , which also analyzed the diet of Leptodactylus podicipinus , belonging to the same Leptodactylus melanonotus species group, where the prey category with the highest IVI was Coleoptera; however, the L. petersii individuals analyzed in this study had Hymenoptera (Formicidae) as the most representative item.…”
Section: Discussioncontrasting
confidence: 95%
“…The diet of these specimens showed similarities with various works involving the diet of Leptodactylids, such as the work by Piatti & Souza (2011), which showed the Orders Coleoptera and Hymenoptera as the most frequent for Leptodactylus podicipinus individuals from a rice field in the wetlands. In this study, we observed differences in relation to previous studies, for instance, the one by Ceron et al, (2018), which also ana-lyzed the diet of Leptodactylus podicipinus, belonging to the same Leptodactylus melanonotus species group, where the prey category with the highest IVI was Coleoptera; however, the L. petersii individuals analyzed in this study had Hymenoptera (Formicidae) as the most representative item. Regarding the niche width value (0.39), it can be related to the availability of ants in the environment, as those have a great biomass in the tropical forests (Holldobler & Wilson, 1990), becoming then, the most consumed item by the individuals.…”
Section: Discussioncontrasting
confidence: 65%
“…From each of the selected studies data on taxonomic information on anurans (only species identified at least to genus level) and prey categories (usually to order, with exception of the family Formicidae and suborder Isoptera), prey abundance in stomachs as well as country and geographical coordinates of the study site were recorded. In studies of anurans diet, preys are usually identified only at the level of order (categories) because of their fragmentation after consumption, being impossible to a finer identification (Duellman 1978, Toft 1980, Ceron et al 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Menin 2014; Do Couto et al 2018;Coelho et al 2020), frogs (Teixeira and Vrcibradic 2003;Ziegler et al 2003;Sanabria et al 2005;Solé et al 2009;Santana et al 2012;Costa-Pereira et al 2015;Sales et al 2015;Camurugi et al 2017;Ceron et al 2018;Coelho et al 2020), and presumably adventiously ingested plant material (Teixeira and Vrcibradic 2003;Camera et al 2014;Do Couto et al 2018;Coelho et al 2020). The Smoky Jungle Frog, L. pentadactylus, is a large Neotropical anuran, occurring along the Amazon Basin in preserved forest and urban forest fragments of Bolivia, Brazil, Colombia, Ecuador, French Guiana, Peru, and Suriname (Heyer 2005;Menin et al 2010;Do Couto and Menin 2014;Do Couto et al 2018).…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ymentioning
confidence: 99%
“…Frogs of the genus Leptodactylus are opportunistic and generalist predators with a variable diet, including small mammals (Ziegler 2003;Coelho et al 2020), insects (Teixeira and Vrcibradic 2003;Ziegler et al 2003;Maneyro et al 2004;Sanabria et al 2005;Solé et al 2009;Sugai et al 2012;Zaracho et al 2012;Camera et al 2014;Camurugi et al 2017;Ceron et al 2018;Do Couto et al 2018;Ganci et al 2018;Solé et al 2018;Baia et al 2020;Montes et al 2020;Oliveira-Souza et al 2020), arachnids (Teixeira and Vrcibradic 2003;Ziegler et al 2003;Maneyro et al 2004;Solé et al 2009;Sugai et al 2012;Zaracho et al 2012;Camera et al 2014;Costa-Pereira et al 2015;Camurugi et al 2017;Ceron et al 2018;Do Couto et al 2018;Solé et al 2018;Baia et al 2020;Montes et al 2020;Oliveira-Souza et al 2020), molluscs, annelids, myriapods (Teixeira and Vrcibradic 2003;Solé et al 2009;Sugai et al 2012;Zaracho et al 2012;Ceron et al 2018;…”
mentioning
confidence: 99%